Effects of climate change on rice production in Malaysia. - Yong, Eu Fan; Said, Salim (1990)
This paper attempts to examine the effect of climate change on rice production in the Muda Area in Malaysia. This was achieved through computer simulation techniques using the CERES-Rice model. The CERES-Rice model and its input parameters with reference to the study area are described briefly. Various runs had been performed with different combinations of soils, seasons, planting methods, irrigation options and fertilizer applications. The corresponding runs using the postulated GISS climate scenario due to a doubling of CO2 concentration in the atmosphere as the source of climate change were also carried out. The results obtained indicate that an average yield reduction ranging from 12% to 22% can be expected under the postulated GISS climate. The maturation period of the rice crop is also expected to shorten by 5 to 10 days. Under the GISS climate, the irrigation water demand is predicted to increase by 15% for the direct seeded rice. However, the irrigation demand for transplanted rice does not show any consistent results and this aspect needs to be studied further.